Study of Thyroid Function in Housewives with Chronic and Relapsing Hand Eczema - Sharma M.D., Dr. Rahul Kumar; Sharma D.M., Dr. Rajendra Kumar (International Journal of Innovative Research in Medical Science, 2017)
Thyroid hormones are playing a critical role in regulating the healthy condition of skin. Thyroid gland abnormality can lead to a diversity of manifestations in skin. We performed thyroid function tests in housewives with chronic and relapsing hand eczema affecting both hands to find prevalence of thyroid dysfunction in them. So far in our knowledge this is the first study in the world evaluating thyroid function tests in housewives with chronic and relapsing hand eczema. Our study showed that out of eighty eight housewives with chronic and relapsing hand eczema twenty one had clinical hypothyroidism (23.9%) and nine had subclinical hypothyroidism (10.2 %). We concluded that there is high prevalence of hypothyroidism in housewives with chronic and relapsing hand eczema involving both hands. The chronic and relapsing hand eczema may be a subtle sign of underlying hypothyroidism, which has to be confirmed by further studies.